Decentralized energy in Water-Energy-Food Security nexus in developing countries: Case studies on successes and failures - Dawit Guta; Jose Jara; Narayan Adhikari; Chen Qiu; Varun Gaur; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2015)
Access to modern energy is vital for sustainable development. In rural areas, decentralized energy solutions may play a significant role in reducing poverty, supporting community institutions and facilitating the generation of basic services such as communication, water access, education and health services. However, the majority of dwellers in off-grid communities in developing countries have little or no access to modern energy technologies, although they are endowed with a vast potential of renewable energy resources. Decentralized energy solutions could serve as an option to solve this energy access problem. However, the previous literature indicates that there are financial, technical, infrastructural, and institutional constraints to scale up decentralized energy options. This paper seeks to study the underlying factors behind the successes and failures of household- and community-based decentralized energy technologies through local case studies from different parts of the world, analyzed through the lenses of the Water-Energy-Food Security (WEF) nexus. First, the paper reviews the literature on the main benchmarks used to evaluate the success and failure of community-based energy. Second, the conceptual framework relating decentralized energy to the WEF nexus elements is briefly described. Thirdly, the methods and data used in the paper are described, followed by the presentation of the case studies. Lastly, the paper is concluded by drawing policy lessons and recommendations. Further empirical studies are recommended to quantitatively evaluate the impacts of decentralized energy solutions on the welfare of households and communities within the framework of the Water-Energy-Food nexus.
Keywords: O13; Q40; 330; decentralized energy; Water-Energy-Food Security nexus